2006
DOI: 10.1253/circj.70.536
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic and Clinical Outcome in ST-Segment Elevation Myocardial Infarction Patients Receiving an Adjunctive Double Bolus Regimen of Tirofiban for Primary Percutaneous Coronary Intervention

Abstract: rimary percutaneous coronary intervention (PCI) in patients with acute myocardial infraction (AMI) has been shown to be preferable to thrombolytic therapy in terms of patient survival, higher rates of patency in the infarcted arteries, and lower rates of reinfarction and stroke. 1,2 These benefits of PCI can be further enhanced by administration of platelet glycoprotein IIb/IIIa inhibitors abciximab 3-7 or eptifibatide. 8,9 Tirofiban 10 stands out as a potentially useful adjunct to PCI because it is a small no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…28 However, significantly better clinical outcomes were not observed in patients administered high doses of tirofiban compared with those in patients administered the conventional dose during short-term and long-term follow-up. 29,30 Furthermore, patients administered a higher dose of tirofiban likely experienced a greater level of platelet inhibition and improved incidence of SR with less myocardial damage and its sequelae. However, due to its questionable benefits and potential risk of increasing bleeding events, it remains unclear whether a higher dose tirofiban therapeutic strategy translates into better clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, significantly better clinical outcomes were not observed in patients administered high doses of tirofiban compared with those in patients administered the conventional dose during short-term and long-term follow-up. 29,30 Furthermore, patients administered a higher dose of tirofiban likely experienced a greater level of platelet inhibition and improved incidence of SR with less myocardial damage and its sequelae. However, due to its questionable benefits and potential risk of increasing bleeding events, it remains unclear whether a higher dose tirofiban therapeutic strategy translates into better clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a more recent study of ST-segment elevation ACS, a double-bolus intravenous regimen of tirofiban did not demonstrate significant angiographic or clinical outcomes in patients undergoing PCI. 18 The 30-day ventricular function and cardiac events following primary PCI are determined by a number of factors, such as the size of the infarct, the status of coronary reperfusion, the use of medications, and presence of serum inflammatory factors such as interleukin-10. 1,2,19 In the present study, there were no significant differences between the study and the control groups in the baseline patient characteristics, plasma levels of CK-MB and cTnT, the time interval from onset of chest pain to PCI or the use of medications.…”
Section: Discussionmentioning
confidence: 99%
“…The use of tirofiban was not an independent indicator for slow/no reflow, which significantly improves the initial TIMI. The effects of preoperative treatment with tirofiban on the prognosis of acute coronary syndrome (ACS) patients were extensively investigated in the past two decades, but the results were inconsistent [15, 26]. Skyschally et al reported that distal coronary embolization was associated with severe regional contractile dysfunction in animal model [27]; we also found that the value of LVEF after PCI was remarkably lower in patients with slow/no reflow than that in normal reflow.…”
Section: Discussionmentioning
confidence: 77%